Experimental and numerical study on performance of precast concrete wet and dry joints under progressive collapse scenario - Bao, Yintong (2023)
Structural collapse events induced by extreme loads have grabbed the attention of building regulatory institutions worldwide. Compared with conventional cast-in-situ reinforced concrete (RC) structures, precast concrete (PC) buildings are more prone to progressive collapse scenario due to inherent weakness in continuity of reinforcement in beam-column joints. With increasing demand for productivity, PC construction has become commonplace in countries where labour cost is high. Therefore, investigations on the structural behaviour of PC beam-column joints under collapse scenarios are necessary. In the present study, six half-scaled PC beam-column joints with one type of PC wet joint detailing and two types of PC mechanical dry joint details were tested for progressive collapse under interior column removal scenario. The PC wet joint employed an external corbel and on-site installation of mid-height reinforcing bars between the PC beam and the corbel. One type of PC dry joints applied steel beam shoe connections and a built-in corbel, simulating semi-rigid joint, while another type involved dowel rod connections and bolted top seat angle as a simple joint. The load-carrying capacity, deformation capacity, mobilisation of catenary action (CA) and failure mode were presented and discussed. The experimental results showed that the PC beam-column joints with wet detailing attained excellent hogging and sagging moment capacities, as well as sufficient plastic ductility for developing CA to provide a subsequent increase in structural resistance at large deformation stage. However, due to premature failure of the welded connection in beam shoes and reduced ductility caused by thermal damage of longitudinal bars near the welded connection, the two types of PC dry joints investigated could only achieve limited ductility and could not develop CA at large deformation stage. Based on the failure mode of each type of PC joint, different component-based joint models (CBM) were developed and verified by the six test results. Thereafter, parametric studies based on the verified CBMs indicated that reduced ductility of the top and bottom reinforcement at the precast interface could highly affect the development sequence and structural capacity of different CA mechanisms. Besides, inevitable gaps at the precast interface could remarkably reduce compressive arch action but have negligible influence on CA of the PC sub-assemblages.